“BE YOURSELF” (The Creation of a Music Composition) - Asep Saepul Haris; Rahayu Supanggah; Pande Made Sukerta; Bambang Sunarto (LP2M ISBI Bandung, 2017)
AbstractAn artistic workmanship is a creative work process of an artist in creating artworks. Artwork meant by the writer is